Use of Cystorelin® and artificial insemination in repeat-breeding beef heifers after estrous synchronization - Holz, J.P.; Houghton, P.L.; Spire, M.F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Gonadotropin-releasing hormone (GnRH) was administered to a group of 13- to 14- month-old Angus and Angus crossbred repeat-breeding heifers at the time of the second or third artificial insemination to determine its effect on conception rates. Little benefit was derived from the use of GnRH at either second or third service in highly developed repeat-breeding heifers.
Keywords: Beef; Gonadotropin-releasing hormone; Repeat breeders; Conception rate; Beef heifers